From signals to stem cells and back again - Janocha, Denis; Lohmann, Jan U. (Current opinion in plant biology, 2018)
During plant development, organ morphology and body architecture are dynamically adjusted in response to a changing environment. This developmental plasticity is based on precisely controlled maintenance of primary, as well as programmed initiation of pluripotent stem cell populations during secondary- and de novo meristem formation (reviewed in [1, 2, 3]). Plant stem cells are found exclusively in specific locations that are defined by relative position within the growing tissue. It follows that stem cell fate is primarily instructed by endogenous signals that dynamically define the stem cell niche in response to tissue topography [4]. Furthermore, plant stem cell activity is strongly dependent on developmental stage, suggesting that they are sensitive to long range signaling from distant organs, including the root [5,6••]. And finally, environmental signals exert a major influence allowing plants to cope with the plethora of highly variable environmental parameters during their life-cycle [7]. Integrating tissue level positional information with long range developmental cues, as well as environmental signals requires intricate molecular mechanisms that allow to filter, classify, and balance diverse inputs and translate them into appropriate local cell behavior. In this short review, we aim to highlight advances in identifying the relevant signals, their mode of action, as well as the mechanisms of information processing in stem cells of the shoot apical meristem (SAM).
Gesehen am 27.02.2020